2021
DOI: 10.9770/jesi.2021.8.4(40)
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the public debt of a country on the sustainable development of entrepreneurship

Abstract: It is substantiated that as of today the transition to the concept of debt sustainability, which affects the sustainable development of entrepreneurship, is dominant over other areas. The purpose of the study is scientific substantiation of the ways of transformation of debt management in Ukraine, taking into account the experience of EU countries, strengthening of the medium-term aspect of public and stateguaranteed debt management for the purpose of enhancement of sustainable development of entrepreneurship.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Garba and Abdullahi (2013) pointed to a positive and long-term relationship between public spending and economic growth. Zhuravlov et al (2021), based on the experience of Hungary, Poland, Bulgaria, and Latvia, showed that appropriate debt management affects the sustainable development of entrepreneurship and the entire country. Citizens increasingly aware of the importance of the impact of human activities on the environment accept the growing public spending on environmental protection, including the implementation of modern, pro-ecological technologies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Garba and Abdullahi (2013) pointed to a positive and long-term relationship between public spending and economic growth. Zhuravlov et al (2021), based on the experience of Hungary, Poland, Bulgaria, and Latvia, showed that appropriate debt management affects the sustainable development of entrepreneurship and the entire country. Citizens increasingly aware of the importance of the impact of human activities on the environment accept the growing public spending on environmental protection, including the implementation of modern, pro-ecological technologies.…”
Section: Literature Reviewmentioning
confidence: 99%